Metropolizacja a kwestia wspólnot obywatelskich - Pająk, Marek (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
This article explores the process of metropolisation and its growing impact on civil communities. It is the analysis of relations between the city - seen as a community where civil values are constituted – and numerous changes caused by evolving roles of large metropolises. The article traces the evolution of the idea of the City back to the Ancient Greece and the origins of the Western Civilisation. It focuses on the fundamental problems and possibilities connected with the metropolisation process. The author is concerned with consequences of the metropolisation such as the decline of civil values and decrease in political participation
Keywords: metropolizacja; wspólnota; miasto; polis